Investment Decision in Indonesia Stock Exchange: The Demographic of Environmental, Social, and Governance Investors - Yanuar Trisnowati; Noer A. Achsani; Roy Sembel; Trias Andati (Universitas Pasundan, 2023)
Current investment decisions in stocks need to consider environmental, social, and governance factors in their investment analysis, in addition to considering aspects of the level of return and risk. The study aims to analyze who invests in Environmental, Social, and Governance (ESG) that fits a particular profile and whether that profile differs significantly from that of ordinary investors. In this survey, 415 individual Indonesian investors were surveyed. Survey respondents include those who invest according to ESG principles and those who are not interested in ESG, to determine if there are demographic differences. The research method used in the research is to use analysis of variance (ANOVA). The paper finds that the ANOVA assumption on the test of homogeneity variance states that the independent variable group has the same variance. Age variable has a significant effect on investment decisions. Meanwhile, gender, education, experience, and amount of investment variables do not affect investment decisions in ESG and non-ESG stocks. The demographic profile of investors who invest in ESG stocks has a significant difference to investors who make decisions to invest in non-ESG stocks. This study contributes to investors considering ESG factors in their investment decisions, and companies must also run their operations more with ESG principles.